2012
DOI: 10.1039/c2em10705h
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of building façade road traffic noise levels in Flanders

Abstract: The evolution of daytime façade noise levels by road traffic at 250 dwellings in Flanders is assessed. Three identical man-operated measurement campaigns have been conducted in the years 1996, 2001 and 2009, during fall. A practical methodology has been developed, based on short time noise measurements and context observations at these locations. The uncertainty introduced by short-term sampling has been quantified as a function of the noise level. Furthermore, a correction is proposed for measuring at a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Over 10 % is severely disturbed, with significant health impacts (Stassen, Collier et al 2008). Approximately 30 % of building facades have a noise exposure over 65dBA during daytime (Van Renterghem, Botteldooren et al 2012). Noise exposure maps from major traffic roads are available from the Flemish Agency for Roads and Traffic.…”
Section: Noise Reductionmentioning
confidence: 99%
“…Over 10 % is severely disturbed, with significant health impacts (Stassen, Collier et al 2008). Approximately 30 % of building facades have a noise exposure over 65dBA during daytime (Van Renterghem, Botteldooren et al 2012). Noise exposure maps from major traffic roads are available from the Flemish Agency for Roads and Traffic.…”
Section: Noise Reductionmentioning
confidence: 99%
“…In addition, noise pollution is a major source of complaints [1], especially in densely populated areas. Repeated extensive measurement campaigns in the period 1996–2009 in Flanders (Belgium) hardly showed any improvement in the noise exposure measured as equivalent levels in front of the façade [3]. As a result, it can be concluded that road traffic noise is a persistent and major environmental problem.…”
Section: Introductionmentioning
confidence: 99%
“…This study is concerned with road traffic noise, as this is the most widespread environmental noise source in the region under study [3]. We opted for a face-to-face questionnaire (interview) since it allows gathering more detailed information as discussed further in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Single 20 min observations showed to yield stable conditions at locations where the noise level and consequently the traffic intensity were of practical interest. Spreading the time interval to, e.g., 1 h was considered unnecessary because, within that period, both the traffic conditions and the resulting noise levels were observed not to change significantly during daytime [67]. This was confirmed through long-term measurements carried out during other experimental tests in Ancona.…”
Section: External Noise Measurementmentioning
confidence: 79%
“…Hence, measurements were carried out during daytime (between 7:00 am and 07:00 pm), since road traffic noise exposure (in particular for the façades giving directly onto the road, i.e. RF 1, RF 2, and RF 3) is more significant during that time interval [67]. In particular, since outdoor noise due to traffic is time fluctuating, it was chosen to measure the equivalent sound pressure levels during the peak-hour of the day (when more traffic was observed).…”
Section: External Noise Measurementmentioning
confidence: 99%